Computer use pattern among adolescent school students in Chennai - Muthuthandavan, Anitha Rani; Christado, Sathiyasekaran Bernard Winfred (Indian Journal of Community Health, 2014)
Background: Computer use among adolescents is increased during the recent years. Computer has become important social medium for adolescents. The study was carried out to assess the computer use pattern among adolescent school students in Chennai. Methods: This is a cross sectional study done among 1842 adolescent school students studying in secondary and higher secondary schools in Chennai. Data was collected by self-administered questionnaire. Results: There were 895 boys and 947 girls included in this study. Nearly 18% of adolescents were using computer for more than 3 hours. Nearly 35% of adolescents were non users of computer. In this study computer use duration was more among boys than girls. Significant difference was observed in pattern of computer use. High proportion of adolescents use computer for academic purpose. Conclusion: Greater proportion of adolescents use computer for longer hours which need to be restricted for prevention of long term adverse health consequences.